Modalitas Anggota DPRD dalam Kontestasi Politik : (Studi Kasus: Kemenangan Yermias Y.K Pellokila.Sh sebagai Anggota Terpilih DPRD pada Pemilu Legislatif Tahun 2024 di Dapil II Kabupaten Kupang) - Fentry Trieputry Tungga; Yeftha Y. Sabaat; Frans W. Muskanan; Diana S.A.N Tabun (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2025)
In the order of Democracy, there is an election system intended to elect representatives of the people, one of which is election contestation. Elections are a contestation arena for candidates for people's representatives such as legislative candidates for DPRD members. So that legislative candidates must prepare themselves with qualified capital such as political modalities. Political capital according to pierre bourdiue's theory is capital consisting of 5 capitals, namely political capital, social capital, economic capital, symbolic capital and cultural capital. In this study, researchers wanted to see how the winning modality of Yermias Y. K. Pellokila, SH as an elected member of the DPRD in the 2024 legislative elections in district II Kupang Regency. With the aim of knowing and describing in depth the use of what modalities Yermias Y. K. Pellokila, SH used in achieving victory. This research uses a qualitative approach with a descriptive-analytic approach, with data collection techniques through documentation studies and interviews. The results of this study state that of the 5 capitals owned by Yermias Y.K Pelokilla SH, namely political capital, social capital, economic capital, cultural capital and symbolic capital and there are 2 most influential capitals used by Yermias Y. K. Pellokila, SH in winning the 2024 legislative elections in district II Kupang Regency, namely social capital and symbolic capital. In the victory of Yermias Y.K Pellokila SH in social capital there is a form of family support that is very extraordinary with the formation of a family team as a substitute for a success team, a family arisan community group, participating in community events and the Pellokila,SH family background being the hallmark of YeremiasY.K Pelokilla SH to be able to win the hearts of the community. And in the symbolic capital of Yermias Y.K Pellokila,SH self-authorship is reflected in his life track record and his name which is well known to the public as a firm person, has a good performance as a former head of Pariti village to be a benchmark for public trust in Yermias Y.K Pellokila,SH and bring him to win the seat of DPRD Member for the 2024 Legislative Election in district II Kupang Regency.